Ionizing radiation-mediated dendritic cell maturation exacerbates inflammatory response of bone marrow mesenchymal stem cells and impairs osteogenesis in radiation-induced jaw injury - Mengting Zheng; Heng Chen; Zhonglong Liu; Zhouyang Wang; Ting Jiang; Yue He (Stem Cell Research & Therapy)
Abstract Background Radiation-induced jaw injury is one of the most severe complications after radiotherapy for head and neck cancer, which can disrupt patients’ health and quality of life. Although the direct target of inflammation and suppressed bone regeneration activity by ionizing radiation (IR) has been phenomenally observed, the underlying mechanisms and potential therapeutic targets remain blurred. Osteoimmunology emphasizes that dendritic cells (DCs) may contribute to bone diseases. Methods In this study, we assessed phenotypic and functional alterations of DCs in a radiation-induced jaw injury rat model through immunohistopathological staining. The effects of IR on bone marrow-derived dendritic cells (BMDCs) in vitro were further validated by flow cytometry, ELISA, mixed lymphocyte reaction (MLR) assay, and transwell. The cellular responses and differentiation of bone marrow mesenchymal stem cells (BMSCs) under BMDC-derived conditioned medium stimulation were evaluated through various cell staining, Quantitative real-time polymerase chain reaction (qRT-PCR), and western blotting. Flow cytometry, qRT-PCR, WB were employed to verify tolerogenic characteristics of Vitamin D3 (VitD3)-induced tolerogenic DCs (tolDCs). TolDCs were encapsulated in GelMA to develop an effective in vivo therapeutic approach for irradiated jaw defects. Results We revealed that IR activated the mature-inflammatory phenotype and corresponding biological functions of DCs through the nuclear factor kappa-B (NF-κB) signaling pathway. Exposure to conditioned medium from irradiated BMDCs induced oxidative stress and inflammatory responses in BMSCs, inhibiting their proliferation, migration, and osteogenic potential while potentiating adipogenic capacity. Furthermore, tolDCs were proven to be resistant to radiation-induced activation. Local administration of tolDCs was effective in improving bone regeneration of irradiated jawbone defects. Conclusions Hyperactivation of DCs served as a potential pathogenic factor in radiation-induced jaw injury, exacerbating local inflammation and abrogating the biological functions of BMSCs. The local transplantation of tolDCs was a promising therapeutic strategy for osteogenesis in radiation-induced jaw injury.